Successful embolisation of an intracranial meningioma via a right-sided aortic arch - Das, Deep (BMJ Case Rep, 2017)
Right aortic arch is an unusual arch variation. Supra-aortic neurointervention in such cases has been sparingly reported. This case highlights the unusual association of a left hemispheric convexity meningioma with a right aortic arch which was successfully navigated. Particle embolisation of the meningioma produced good results followed by complete surgical excision and gratifying overall final outcome in this challenging scenario.